A Critical Review on the Book The East Asian Development Experience: The Miracle, The Crisis and the Future - Zahra Karimi Moughari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The East Asian Development Experience: The Miracle, The Crisis and The Future is written by Ha Joon Chang and is translated into Persian by Leila Sadat Fatemi Nasab. The book explains the causes of successful development in East Asian countries. These countries which were poor and backward after the Second World War, during a few decades, became newly industrializing countries. There are different views about the causes of the development of East Asian countries. Some experts believe that the major cause is their acceptance of market mechanisms and export orientation. While others emphasize the governments' role in supporting infant industries and encouraging the private sector exports. Chang shows that free-market mechanism was not the cause of their success. Conversely, governments' conditional supporting measures alongside effective supervision on the private sector economic performance, and emphasis on exports had a major impact in the development of the East Asian countries. “The East Asian Development Experience: The Miracle, The Crisis and The Future” is a very useful book for Iranian researchers and policymakers in the current situation. Fatemi Nasab's translation of the book is very good but there are a few problems in translating special words that seem to be related to the lack of deep knowledge in economics.